The Soviet century - Lewin, Moshe 1921-2010 (Verso, 2005)
The story of the Soviet Union is a complex one, and one that was for a long time inaccessible to western historians due to lack of documentation and ideologically motivated obfuscation, but it is one that Moshe Lewin is uniquely qualified to tell.